Profile of respiratory problems in patients attending a tertiary care center OPD - A study from central India - Dubey, Ashish; Sharma, Parag (International Journal of Medical Research and Review, 2015)
Introduction: The top four respiratory diseases, lower respiratory tract infections, chronic obstructive pulmonary disease (COPD), tuberculosis, and lung cancer, are among the ten leading causes of death worldwide. Methodology: A Hospital based cross-sectional study carried out in the Department of Tb and Chest of Chirayu Medical College and Hospital, Bhopal located in central India. All the patients, who visited hospital out-patient department during the period January 2013 to December 2014, with complaints of respiratory illness were included in the study. Results: Out of total 1690 patients, most commonly observed respiratory disease is URTI, which was seen in 642(37.99) patients, followed by asthma which was seen in 436(25.8%) of the patients. Less common findings were haemoptysis, chest pain and lymphadenopathy of undiagnosed etiology which was seen in 24(1.42%), 11(0.65%) and 08(0.47%) of the patients respectively. Conclusion: Most of the cases of respiratory diseases belong to geriatric age group. So, there is a need towards targeting the health resources in prioritizing the respiratory illness among geriatric population.